Analysis Of Water Loss Due To Seepage In The Irrigation Channel Of Batu Bulan Dam Sumbawa NTB - Didin Najimuddin; Imam Wahyudi; Soedarsono Soedarsono (International Journal Labs, 2024)
This study aims to analyze water loss due to seepage in the irrigation canal of the Batu Bulan Dam in Sumbawa, NTB. Irrigation systems are vital for agriculture in Indonesia, but water loss from seepage significantly reduces water use efficiency. The Batu Bulan Dam plays a crucial role in supporting agriculture in the region, yet the poor physical condition of the canal, cracks, and high soil permeability cause substantial water seepage. This study uses Geo-Studio Seep/W 2018 software to model and analyze water seepage patterns in the canal. The results reveal that water loss due to seepage is significant, influenced by the canal's physical condition and surrounding soil properties. This loss negatively impacts agricultural productivity and the environment. Plants that do not receive adequate water suffer from drought stress, leading to reduced crop yields and lower product quality. Additionally, a decrease in groundwater levels can disrupt groundwater ecosystems. To improve irrigation efficiency, it is recommended to upgrade the canal to a permanent structure, conduct regular maintenance, and adopt advanced monitoring technologies. Dewatering and proper drainage management are also necessary to lower groundwater levels. Using protective layers and soil stabilization around the canal can reduce permeability. Furthermore, education and training for irrigation workers and farmers are essential for efficient water management. The findings from this study are expected to provide a foundation for developing effective solutions to reduce water loss from seepage, thereby supporting agricultural sustainability in Sumbawa, NTB.